Apolipoprotein L1 variability is associated with increased risk of renal failure in the Czech population - Hubacek, Jaroslav A; Hruba, Petra; Adamkova, Vera; Pokorna, Eva; Viklicky, Ondrej (Gene, 2022)
BACKGROUND: With stage 5 chronic kidney disease (CKD5) more prevalent in the Czech Republic than in most European countries, genetic susceptibility is potentially implicated. METHODS: In a group of 1489 CKD5 kidney transplantation patients (93% with complete clinical characteristics; mean age 52.0 years, 37% females) and 2559 healthy controls (mean age 49.0 years, 51% females), we examined the prevalence of six APOL1 SNPs (rs73885319, rs71785313, rs13056427, rs136147, rs10854688 and rs9610473) and one newly detected 55-nucleotide insertion/deletion polymorphism. RESULTS: The rs73885319 and rs71785313 variants were monomorphic in the Czech Caucasian population. Genotype frequencies of the three SNPs examined (rs13056427, rs136147 and rs9610473) were almost identical in patients and controls (all P values were between 0.39 and 0.91). Minor homozygotes of rs10854688 were more common between the patients (13.2%) than in controls (10.7%) (OR [95% CI]; 1.32 [1.08-1.64]; P < 0.01). Prevalence of the newly detected 55-bp APOL1 deletion was significantly higher in CKD5 patients (3.0% vs. 1.7%; OR [95% CI]; 1.80 [1.16-2.80]; P < 0.01) compared to controls. Frequencies of some individual APOL1 haplotypes were borderline different between patients and controls. CONCLUSION: We found an association between rs10854688 SNP within the APOL1 gene and end-stage renal disease in the Czech Caucasian population. Further independent studies are required before a conclusive association between the newly detected APOL1 insertion/deletion polymorphism and CKD5 can be confirmed.
Keywords: renální insuficience; dospělí; cyklin-dependentní kinasa 5; Female; Apolipoprotein L1; Restriction Mapping; černoši; Adult; ženské pohlaví; jednonukleotidový polymorfismus; lidé; mutace INDEL; Polymorphism, Single Nucleotide; genetická predispozice k nemoci; studie případů a kontrol; Genetic Predisposition to Disease; apolipoprotein L1; INDEL Mutation; Genetic Variation; Risk Factors; Male; Case-Control Studies; Aged; Haplotypes; Czech Republic; Black People; rizikové faktory; Česká republika; lidé středního věku; senioři; haplotypy; mužské pohlaví; Renal Insufficiency; genetická variace; restrikční mapování; Middle Aged; Cyclin-Dependent Kinase 5; Humans